PENGARUH TARIF PAJAK DAN KEBIJAKAN DIVIDEN TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2021-2023 - Robin Solala Putra Hia; Hendrik E.S Samosir; Danri Toni Siboro (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2025)
This research aims to assess the impact of tax rates and dividend policies on stock prices in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. Stock price is considered a key indicator that reflects a company's market valuation from the perspective of investors, making it essential to explore the underlying factors influencing price fluctuations for sound investment decisions. The study adopts a quantitative method with an associative design. A total of 40 manufacturing companies were selected using purposive sampling based on specific criteria. Data analysis was conducted using multiple linear regression, assisted by SPSS version 27. The findings reveal that neither tax rates nor dividend policies have a statistically significant partial influence on stock prices. The t-test results show significance values of 0.087 for tax rates and 0.574 for dividend policies, both of which exceed the standard threshold of 0.05. Furthermore, the coefficient of determination (R²) is 0.052, indicating that only 5.2% of the variation in stock prices is explained by the two independent variables, while the remaining 94.8% is influenced by other factors outside the model. These results suggest that tax rates and dividend policies are not the dominant determinants of stock price movements among manufacturing companies during the observed period. It is therefore recommended that future studies incorporate additional relevant variables and broaden the sample coverage to yield more comprehensive insights.